Gauging the Impact of Gender Grammaticization in Different Languages: Application of a Linguistic-Visual Paradigm - Sato, Sayaka; Gygax, Pascal M.; Gabriel, Ute (Frontiers in Psychology, 2016)
Employing a linguistic-visual paradigm, we investigated whether the grammaticization of gender information impacts readers’ gender representations. French and German were taken as comparative languages, taking into account the male gender bias associated to both languages, as well as the comparative gender biases associated to their plural determiners (French: les [generic] vs. German: die [morphologically feminine]). Bilingual speakers of French and German had to judge whether a pair of facial images representing two men or a man and a woman could represent a gender stereotypical role noun prime (e.g., nurses). The prime was presented in the masculine plural form with or without a plural determiner. Results indicated that the overt grammaticization of the male gender in the masculine form dominated the representation of the role nouns (though interpretable as generic). However, the effect of the determiner was not found, indicating that only gender information associated to a human reference role noun had impacted readers’ representations. The results, discussed in the framework of the thinking-for-speaking hypothesis, demonstrated that linguistic-visual paradigms are well-suited to gauge the impact of both stereotype information and grammaticization when processing role nouns. Keywords: gender representation, gender stereotypes, grammatical gender, generic masculine, thinking-for-speaking hypothesis, bilingualism